SOSIALISASI KEMITRAAN PEMBELAJARAN ANTARA SEKOLAH, GURU DAN ORANG TUA DALAM IMPLEMENTASI PEMBELAJARAN MENDALAM DI SDN 274 MALUKU TENGAH - Limba, Anatasija; Latununuwe, Altje; Huliselan, Estevanus Kristian; Malawau, Seska; Tamaela, Elsina Sarah; Singerin, Sarlota; Sapulete, Heppy; Latupeirissa, Asry Nelannya; Nirahua, Juliana; Suharlan, Lisa Sutami; Latumakulita, Ivandra Immanuela; Souisa, Cinta Amergebi; Aprilia, Yulianty; Aswaly, Felisia Anggryani (Universitas Pattimura, 2025)
The socialization of partnerships between teachers and parents in the implementation of deep learning is a strategic effort to build a collaborative educational environment centered on students’ needs. The main goal of this activity is to strengthen mutual understanding of the importance of synergy between teachers and parents in supporting a meaningful, reflective, and sustainable learning process. The socialization was carried out through discussions, counseling sessions, and the exchange of experiences and best practices between schools and parents. The results show that open communication and strong cooperation enhance support for character development, critical thinking skills, and students’ learning independence. Furthermore, this activity fosters a shared commitment to creating a positive learning atmosphere both at school and at home. Therefore, collaboration between teachers and parents in deep learning serves as a key element in improving the quality of education and can be used as a model for other schools, especially in areas with similar socio-cultural and geographical conditions.